The E-Filing Tax Implementation Success Examined From The Taxpayer Agency as User - Windriati Windriati; M. Husni Thamrin; Nurmah Semil (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aimed at analyzing the effect of system quality, information quality, and service quality to the implementation of e-Filing tax system on net benefits with user satisfaction as an intervening variable at the Pratama Palembang Ilir Barat Tax Service Office (TSO). This research was a quantitative study with survey approach through distributing questionnaires to 350 respondents as samples. To analyze the data, Covariance Base Structure Equation Modeling (CB-SEM) was used. The results indicated that the quality of systems, information and service positively and significantly affected the user satisfaction with the percentage of 16%, 20%, and 26%, respectively. Likewise, the e-Filing user satisfaction had a positive and significant effect on the net benefits with the percentage of 64%. The results of this study recommend that, despite its being mandatory, the implementation of e-Filing system could provide satisfaction to the users. This indicated that the system is currently as expected; not only due to its being mandatory, but the users satisfaction also contributed to the system’s sustainability. The output of the services provided in the form of taxpayer compliance, however, has not shown optimal results. Thus, a continuous reformation of the system, information, and service quality is hoped to be conducted.